Educational Interventions to Improve Advance Care Planning Discussions, Documentation and Billing. (April 2021) - Henage, Cristine B.; McBride, J. Marvin; Pino, Joseph; Williams, Jessica; Vedovi, Jill; Cannady, Nicole; Buno, Liz Riley; Chatman, Toni; Busby-Whitehead, Jan; Roberts, Ellen
Background/Objectives: To determine the impact of educational interventions, clinic workflow redesign, and quality improvement coaching on the frequency of advance care planning (ACP) activities for patients over the age of 65. Design: Nonrandomized before-and-after study. Setting: 13 ambulatory care clinics with 81 primary care providers in eastern and central North Carolina. Participants: Patients across 13 primary care clinics staffed by 66 physicians, 8 physician assistants and 7 family nurse practitioners. Interventions: Interprofessional, interactive ACP training for the entire interprofessional team and quality improvement project management with an emphasis on workflow redesign. Measurements: From July 2017 through June 2018—number of ACP discussions, number of written ACP documents incorporated into the electronic medical record (EMR), number of ACP encounters billed. Results: Following the interventions, healthcare providers were more than twice as likely to conduct ACP discussions with their patients. Patients were 1.4 times more likely to have an ACP document included in their electronic medical record. Providers were significantly ( p < 0.05) more likely to bill for an ACP encounter in only one clinic. Conclusions: Implementing ACP education for all clinic staff, planning for workflow changes to involve the entire interprofessional team and supporting ACP activities with quality improvement coaching leads to statistically significant improvements in the frequency of ACP discussions, the number of ACP documents included in the electronic medical record and number of ACP encounters billed.